Investigating the safety of physical rehabilitation with critically ill patients receiving vasoactive drugs: an exploratory observational feasibility study - Woodbridge,HR; Alexander,CM; Brett,SJ; Antcliffe,DB; Chan,EL; Gordon,AC (PLoS One, 2025)
BackgroundPhysical rehabilitation of critically ill patients may improve physical outcomes; however, the relative benefits and risks with patients requiring vasoactive drugs is currently unknown. A feasibility study is needed to inform the design of a future trial required to address this issue.MethodsA two-phase exploratory observational feasibility study was carried out:A retrospective study to clarify the current practice of rehabilitation with patients receiving vasoactive drugs to inform future trial interventions and design.A prospective study exploring recruitment and outcome measurement. Intensive care patients receiving vasoactive drugs were recruited and asked about the acceptability of a future trial. The feasibility of using an adverse event tool was measured during rehabilitation. Patients were followed up after 60 days to describe the feasibility of measuring outcomes for a future trial.ResultsRetrospective study (n = 78): Twenty-one percent of patients took part in physical rehabilitation whilst receiving vasoactive drugs. Of 321 days with vasoactive drugs administered, physical rehabilitation occurred on 27 days (8%).Prospective study (n = 40): Eighty-one percent of participants indicated acceptability of being recruited into a future trial (n = 37). Eighty-eight percent of clinicians found it acceptable to randomise patients into either early rehabilitation or standard care. The adverse event tool was implemented by researchers with 2% loss of information. Finally, a 100% follow-up rate at day 60 was achieved for mortality outcomes. Follow-up rates were 70% for the EQ-5D (5 level), 65% for the World Health Organisation’s Disability Assessment Schedule 2.0 and RAND 36-item Health Survey 1.0 and 26% for the 6-minute walk test.ConclusionsThis study found a low frequency of physical rehabilitation occurring with intensive care patients receiving vasoactive drugs. A high proportion of clinicians and patients found a future RCT within this patient g